Exploring the Impact of Copper Oxide Substitution on Structure, Morphology, Bioactivity, and Electrical Properties of 45S5 Bioglass® - Hammami, Imen (2024)
Funding Information: This research was funded by FEDER funds through the COMPETE 2020 Program and National Funds through the FCT—Portuguese Foundation for Science and Technology under the project LISBOA-01-0247-FEDER-039985/POCI-01-0247-FEDER-039985 of the Associate Laboratory Institute of Nanostructures, Nanomodelling and Nanofabrication—i3N. S.K. Jakka acknowledges the FCT—Fundaçao para a Ciência e a Tecnologia, Portugal, I.P., in the scope of the framework contract foreseen in numbers 4, 5, and 6 of article 23 of the Decree Law 57/2016 of 29 August, changed by Law 57/2017 of 19 July. Publisher Copyright: © 2024 by the authors.